Unique Leishmania mexicana clones secrete populations of extracellular vesicles with unique protein profile and variable infectious capability - Dong, George; Douanne, Noélie; Fernandez-Prada, Christopher; Olivier, Martin (Frontiers in Cellular and Infection Microbiology, 2024)
The study of extracellular vesicles has become an incredibly important field of study, but the inherent heterogeneity of these vesicles continues to make their study challenging. The genetic variability and well-documented protocols for the growth and vesicle isolation from Leishmania parasites provide a unique opportunity to compare the heterogeneity of different populations secreted by Leishmania clones. Leishmania mexicana was cultured on solid SDM agar plates and 8 clonal colonies were selected. The EVs collected from the liquid cultures of these 8 clones were assessed by NTA, TEM, and proteomic analysis. We found that all 8 clonal L. mexicana cultures were visually indistinguishable from each other and had similar growth rate, and these physical similarities extended to their EVs. However, proteomic analysis reveals that the EVs collected have unique protein profiles compared to each other and EVs isolated from a heterogeneous liquid culture of L. mexicana. We selected 3 clonal EVs for further mouse infection experiments and found that EVs from CL7 L. mexicana consistently caused reduced footpad swelling in C57BL6 mice footpads compared to EVs from CL1, CL8, and heterogenous L. mexicana. This trend was not observed when infecting Balb/C mice and C57BL6 with the parasites alone, with only CL1 L. mexicana causing significantly increased infection in Balb/c mice. Our results together show that EVs isolated from different clonal colonies of L. mexicana have distinct differences in protein cargo which can lead to varying outcomes on Leishmania infection. Further evaluation will be needed to determine the underlying mechanisms behind this and verify that differences observed in infectivity are directly caused by variations between our L. mexicana clones, especially genetic sequencing and immunoblotting to validate our results.